Immune Thrombocytopenia Purpura in Children in Lebanon: Prevalence, Treatment Modalities, and Clinical Outcomes in a Retrospective Study - Hassan K. Khalife; Fadi Abdel-Sater; Zaynab Fatfat; Hussein Khalife; Kawthar H. Sharaf Al-Deen; Hala Khalife (Ital Publication, 2022)
Background: Immune thrombocytopenia purpura (ITP) is one of the most common autoimmune diseases in children characterized by a decreased number of circulating platelets combined with impaired platelet production. There is limited literature data on the prevalence and treatment modalities, and outcome of ITP in children from Lebanon. Methods: We retrospectively reviewed the demographic and clinical data of 59 patients aged 0-18 years diagnosed with ITP between January 2007 and April 2016 in different hospitals in Beirut and the south of Lebanon. Results: ITP patients represented 2.5% of the total number of children admitted to these hospitals during this period. Among the ITP children, 55.93% were male and 44.07% were female. The greatest number of ITP children were in the 1-4 year group, followed by the 5-9 year group. As for the clinical course of the disease, 40.68% of the ITP children presented acute ITP, whereas 59.32% presented chronic ITP. Among the different therapeutic approaches adopted to treat these ITP children, intravenous immunoglobulin was the most commonly used, followed by steroids, a combination of these both agents, cyclosporine, and splenectomy. Interestingly, these therapeutic modalities induced a statistically significant increase in the patients' platelet count. In addition, the clinical course of ITP was not significantly associated with each of the age group, the platelet count at diagnosis, and gender of patients. Conclusion:This study showed the prevalence of ITP among children from Lebanon, where more than half of ITP children presented a chronic disease. Further studies are needed to evaluate additional predictors of chronic ITP among children from Lebanon and help medical providers make informed decisions about treating childhood ITP.   Doi: 10.28991/SciMedJ-2022-04-04-02 Full Text: PDF